Food processing operations modeling : design and analysis - Irudayaraj, Joseph , 1961-; Jun, Soojin (CRC Press, 2009)
Focuses on novel food processing technologies of interest relevant to food safety and quality as well as fresh commercialized computational fluid dynamics software to model complex food processing systems. This book offers information on infrared heating of biological materials as well as modeling electrical resistance heating of foods.